PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PREZI PADA SUB KOMPETENSI PENGERITINGAN DESAIN - PRATIWI, ALVIANA CATUR (Universitas Negeri Jakarta, 2021)
Prezi-based Learning media on the design materials are expected to provide innovation in learning media development in a more innovative and creative learning process. This research aims at (1) describe the procedure of learning media based Prezi in the design of the material. (2) describing the feasibility of Prezi-based learning media in the design curation material. This type of research is R&D (Research and Development) with data collection method using media assessment poll through Google form of 35 observer. The results showed that eligibility was well-deserved for use with a percentage yield of 85%. Media appeal can be said to be very attractive with a percentage yield of 82.14%. Media suitability is stated in accordance with the percentage yield of 83.57%. The quality of the media is declared good quality gains percentage yield of 80.28%. Media creativity is very creative with a percentage yield of 84.28%. Based on these results, the research has been able to reduce Prezi-based media that has been adapted to the subject of the design. Keywords: media development, Prezi, design scaling.